THE EFFECT OF FINANCIAL AND ENVIRONMENTAL PERFORMANCE ON FIRM VALUE: THE MODERATING ROLE OF OWNERSHIP STRUCTURE - Hasanah, Salsabila; Indrawati, Novita; Mela, Nanda Fito (Jurnal Magister Akuntansi Trisakti, 2025)
This study aims to investigate the influence of financial and environmental performance on firm value, emphasizing the role of ownership structure as a moderating factor in this relationship. Financial performance is assessed through Return on Assets (ROA), which reflects a company's efficiency in generating profits relative to its total assets. Meanwhile, environmental performance is evaluated using the PROPER rating system, a government-led assessment framework that categorizes companies based on their compliance with environmental regulations and sustainability practices. Firm value is represented by Tobin's Q, a financial ratio that captures market perceptions of a company's overall worth and future growth potential. The moderating variables in this study include managerial ownership, which indicates the proportion of shares held by executives and insiders, and institutional ownership, which refers to stock ownership by investment firms and other institutional investors. This study employs secondary data collected from 54 mining companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Using multiple regression and moderated regression analysis (MRA), the study reveals that financial and environmental performance significantly and positively affect firm value, reinforcing the importance of strong financial health and sustainable environmental practices in driving corporate valuation. Additionally, institutional ownership is found to enhance these positive relationships, suggesting that companies with a higher level of institutional investors may benefit from increased oversight and improved governance mechanisms. However, managerial ownership does not exhibit a significant moderating effect, indicating that the proportion of shares held by company executives does not necessarily alter the impact of financial and environmental performance on firm value. These findings offer important insights into the role of ownership structures in corporate valuation and provide implications for investors, policymakers, and business leaders in optimizing governance strategies to enhance firm value and ensure long-term sustainability.